2018
DOI: 10.1177/1352458518765666
|View full text |Cite
|
Sign up to set email alerts
|

Serum neurofilament light chain is a biomarker of acute and chronic neuronal damage in early multiple sclerosis

Abstract: sNfL indicates acute inflammation as demonstrated by correlation with Gd+ lesions. It is a promising biomarker for neuro-axonal damage in early multiple sclerosis (MS) patients, since higher baseline sNfL levels predicted future brain atrophy within 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
179
3
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(197 citation statements)
references
References 20 publications
10
179
3
5
Order By: Relevance
“…Of particular interest is the proof that sNfL levels can be used to separate not only patients with MS from healthy controls but also to separate patients with MS with and without persistent clinical and subclinical MRI disease activity. 19,29,30 In previous studies, increased sNfL levels in patients with MS have been independently associated with disability and relapse status and suggested to be a predictive marker for future relapses and disability worsening. 17,19 Further data have proved that patients on disease-modifying treatment had lower sNfL levels than untreated patients.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Of particular interest is the proof that sNfL levels can be used to separate not only patients with MS from healthy controls but also to separate patients with MS with and without persistent clinical and subclinical MRI disease activity. 19,29,30 In previous studies, increased sNfL levels in patients with MS have been independently associated with disability and relapse status and suggested to be a predictive marker for future relapses and disability worsening. 17,19 Further data have proved that patients on disease-modifying treatment had lower sNfL levels than untreated patients.…”
Section: Discussionmentioning
confidence: 98%
“…19,29,30 In previous studies, increased sNfL levels in patients with MS have been independently associated with disability and relapse status and suggested to be a predictive marker for future relapses and disability worsening. 17,19 Further data have proved that patients on disease-modifying treatment had lower sNfL levels than untreated patients. 29 In this line, another study found that patients who switched from injectable therapies to fingolimod had significantly lower sNfL levels than staying on injectables.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Elevated neurofilament light chain (NfL) is a more recently discovered biomarker of neurodegenerative diseases, including AD, frontotemporal dementia, amyotrophic lateral sclerosis, and multiple sclerosis (Chatterjee et al, 2018;Gille et al, 2018;Goossens et al, 2018;Siller et al, 2018). An increase in NfL in CSF and blood is interpreted as an indication of ongoing axonal damage (Lee, Taghian, & Petratos, 2014).…”
Section: Neurofilament Light Chainmentioning
confidence: 99%